Population Dynamics of Babul Hoppers (Oxyrachis tarandus Fab) as Influenced by Weather Parameters in North Bihar - Ali, M.S.; Sattar, A.; Chaturvedi, O.P. (Indian Journal of Agroforestry, 2020)
Seasonal incidence and population dynamics of babul hopper, Oxyrachis tarandus Fab. were studied to record the impact of weather parameters during 2000-2001 at Pusa Farm of Rajendra Agricultural University, Pusa, Bihar under Agroforestry conditions. O. tarandus caused 1.4 to 25.5 percent drying of babul twigs during March to June. Mean percentage of the insects ranged from 8.4 to 3.7. The analysis revealed that the pest activity started to buildup their population sem March throatiest April and remained active upto June. The minimum temperature, relative humidity and vapour pressure had significant positive correlation with the population of O. tarandus whereas maximum temperature, rainfall and relative humidity had no significant effect. Regression models explained 79 to 95 percent variability due to weather parameters for babul twigs infestation under agroclimatic conditions of north Bihar.